Influences of Anatomorphological Features of the Portal Venous System on Postsplenectomy Hemodynamic Characteristics in Patients With Portal Hypertension: A Computational Model-Based Study - Wang, Tianqi; Zhou, Zunqiang; Liang, Fuyou (Frontiers in Physiology, 2021)
Splenectomy, as an effective surgery for relieving complications caused by portal hypertension, is often accompanied by a significantly increased incidence of postoperative thrombosis in the portal venous system (PVS). While the underlying mechanisms remain insufficiently understood, the marked changes in hemodynamic conditions in the PVS following splenectomy have been suggested to be a potential contributing factor. The aim of this study was to investigate the influences of the anatomorphological features of the PVS on hemodynamic characteristics before and after splenectomy, with emphasis on identifying the specific anatomorphological features that make postoperative hemodynamic conditions more clot-promoting. For this purpose, idealized computational hemodynamics models of the PVS were constructed based on general anatomical structures and population-averaged geometrical parameters of the PVS. In the models, we incorporated various anatomorphological variations to represent inter-patient variability. The analyses of hemodynamic data were focused on the spatial distribution of wall shear stress (WSS) and the area ratio of wall regions exposed to low WSS (ALS). Obtained results showed that preoperative hemodynamic conditions were comparable among different models in terms of space-averaged WSS and ALS (all were small) irrespective of the considerable differences in spatial distribution of WSS, whereas, the inter-model differences in ALS were significantly augmented after splenectomy, with the value of ALS reaching up to over 30% in some models, while being smaller than 15% in some other models. Postoperative ALS was mainly determined by the anatomical structure of the PVS, followed by some morphogeometrical parameters, such as the diameter and curvature of the splenic vein, and the distance between the inferior mesenteric vein and splenoportal junction. Relatively, the angles between tributary veins and trunk veins only had mild influences on ALS. In addition, a marked increase in blood viscosity was predicted after splenectomy, especially in regions with low WSS, which may play an additive role to low WSS in initiating thrombosis. These findings suggest that the anatomical structure and some morphogeometrical features of the PVS are important determinants of hemodynamic conditions following splenectomy, which may provide useful clues to assessing the risk of postsplenectomy thrombosis based on medical imaging data.